2017
DOI: 10.15414/jmbfs.2017.6.5.1218-1220
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Phenols and Flavonoids Contents of Aqueous Extract of Pelargonium Graveolens Orgin in the North-East Morocco

Abstract: The objective of this work is to characterize the phenols and flavonoids compounds of extracts of Pelargonium Graveolens from North-East Morocco (TAZA) in terms of antioxidant activity. The antioxidant activity of this aromatic plant was determined according to the DPPH radical scavenging assay to suggest it as a new potential source of natural antioxidants. The quantification of phenolics and flavonoids compounds of solvent extracts (diethyl ether and ethyl acetate) were determined spectrometrically. The DPPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The TFC was determined using a colorimetric procedure with the aluminum chloride technique as outlined by [25]. The results were calculated using quercetin as the reference substance and represented as milligrams of quercetin equivalent per gram of dry material (mg QE/g).…”
Section: Determination Of Total Flavonoid Content (Tfc)mentioning
confidence: 99%
“…The TFC was determined using a colorimetric procedure with the aluminum chloride technique as outlined by [25]. The results were calculated using quercetin as the reference substance and represented as milligrams of quercetin equivalent per gram of dry material (mg QE/g).…”
Section: Determination Of Total Flavonoid Content (Tfc)mentioning
confidence: 99%
“…Antioxidants terminate chain reactions by removing free radical intermediates, and inhibit other oxidation reactions by being oxidized themselves. Oxidative stress is the imbalance between the production of reactive oxygen species (ROS) and the ability of antioxidants to detoxify the reactive intermediates or to repair the damage caused by these intermediates [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Boukhris et al investigated the chemical compounds and biological functions of polar extracts and essential oil and showed that β-citronellol as the primary constituent of the oil part and nine flavonoids were identified as well 19 . Ouadi et al studied the P. graveolens extract by using diethyl ether and ethyl acetate as solvent for this purpose 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Pelargomium graveolens L’Hér., popularly known as rose-scented geranium, has been reported by several authors as a good candidate for phytoremediation; in addition, the effect of heavy metals on the yield and quality of its essential oil has been widely investigated [ 38 , 39 , 40 ]. However, in recent years the pharmacological activity of P. graveolens has been increasingly linked also to the leaf content and composition of the pool of antioxidant phenolics [ 27 , 41 , 42 , 43 , 44 ], and much less is known about the influence of heavy metals on the concentration of these compounds. Therefore, the aim of the present study was to verify the tolerance of P. graveolens to Cu toxicity and to test the hypothesis that Cu-induced stress could stimulate the synthesis of antioxidant phenolic constituents, thus improving the medicinal properties of this species.…”
Section: Introductionmentioning
confidence: 99%